Analysis of the rheological properties of mayonnaise sauces obtained with the use of sodium alginate polysaccharide - Sokolan Nina; Kuranova Ludmila; Ershov Mikhaile; Kuranov Dmitry; Grohovsky Vladimir (BIO Web of Conferences)
The article discusses the possibility of using sodium alginate as an additive in emulsified food products - mayonnaise sauce-to improve its functional properties. Sodium alginate, a polysaccharide of plant origin obtained from brown algae of the Barents Sea, is proposed as an optimal prebiotic with the properties of high-molecular-weight dietary fibers for mayonnaise products . Studies of the rheological properties of aqueous solutions of sodium alginate of various concentrations established the level of introduction of polysaccharide as an emulsion stabilizer in the amount of 1.0-2.0 %. Using organoleptic and rheological methods, the effect of the introduction of sodium alginate into the mayonnaise formulation instead of milk powder and chicken eggs on the properties of the finished product was studied. Studies using a modular compact rheometer MCR 302 (AntonPaar, Austria) of the properties of samples of classic mayonnaise and samples of mayonnaise with sodium alginate in concentrations of 1.0 % and 2.0 % have established the dependences of the rheological characteristics of mayonnaise: viscosity on the shear rate; conservation modulus and loss on amplitude; conservation modulus and loss on frequency; shear strain on time under load) and recovery. It was found that mayonnaises with the addition of sodium alginate, in contrast to the classic, exhibit a higher strength and viscosity, which increases with an increase in the concentration of polysaccharide. Studies of the organoleptic properties and the index “emulsion resistance” of mayonnaise for compliance with the regulatory document for products have established that the necessary and sufficient amount of sodium alginate in the mayonnaise recipe is 1.0 %.